Synthesis, electrochemical, in-situ spectroelectrochemical and in-situ electrocolorimetric characterization of non-peripheral tetrasubstituted metal-free and metallophthalocyanines - KOCA, ATIF (ELSEVIER SCI LTD, 2011)
The synthesis of new metal-free nickel zinc cobalt and copper phthalocyanines with four 6-oxyquinoline groups on the non-peripheral position were prepared by cyclotetramerization of a novel 3-(quinolin-6-yloxy)phthalonitrile All new compounds were characterized by the ways of IR, H-1 NMR C-13 NMR and MS spectral data all of which were compatible with the proposed structures Electrochemical properties of metal-free Ni(II) and Zn(II) phthalocyanines were investigated by using cyclic voltammetry and differential pulse voltammetry techniques The metal-free phthalocyanine exhibits two reversible Pc ring-based one-electron reduction couples The NI(II) and Zn(II) phthalocyanines give very similar voltammetric responses with slightly potential shift due to the different metal center (C) 2010 Elsevier Ltd All rights reserved
Keywords: 6 Hydroxyquinoline; Phthalocyanine; Synthesis; Non peripheral; Cyclic voltammetry; Differantial pulse voltammetry; MICROWAVE-ASSISTED SYNTHESIS; POLYMERIC PHTHALOCYANINES; ZINC-PHTHALOCYANINE; SUBSTITUTED COBALT; MANGANESE; MOIETIES; BULKY